A presurgical window-of-opportunity study of metformin in obesity-driven endometrial cancer. (26th February 2015) - Sivalingam, Vanitha; McVey, Rhona; Gilmour, Kyle; Ali, Saad; Roberts, Chris; Renehan, Andrew; Kitchener, Henry; Crosbie, Emma
Abstract: Background: Metformin use is associated with reduced cancer risk in several observational studies of patients with type 2 diabetes. Results from preclinical studies in endometrial cancer show that metformin reduces cellular proliferation by inhibition of the PI3K-AKT-mTOR pathway. We tested the hypothesis that metformin would reduce cellular proliferation in vivo in atypical endometrial hyperplasia and endometrial endometrioid adenocarcinoma. Methods: We recruited women attending gynaecological oncology clinics in Manchester, UK, with atypical endometrial hyperplasia or endometrial endometrioid adenocarcinoma. Women received metformin (850 mg twice daily) or no drug (control) during the 1–4 week presurgical window between cancer diagnosis and hysterectomy according to patient preference. Paired blood and tumour samples were obtained at recruitment and hysterectomy. Cellular proliferation was assessed by Ki-67 proliferation index. Automated scoring on two separate occasions provided consistent replicate scores (SD <10%). This study is registered with the ISRCTN register, number ISRCTN81570194. Findings: Samples from 40 women have been analysed (28 metformin-treated [median age 64 years, IQR 58–69]; 12 control [70, 64–70]). 24 of the patients (60%) were obese. 22 patients (55%) had either undiagnosed diabetes (fasting glucose >7·0 mmol/L, n=4) or insulin resistance (homoeostatic model assessment of insulin resistance >2·8, n=18). Metformin was taken for a median of 20 days (IQR 17–24), and mild gastrointestinal side-effects were reported by 22 metformin-treated patients. In the metformin-treated group, Ki-67 was 12·9% lower at hysterectomy than at recruitment (95% CI 3·7–22·1, p=0·008) after adjustment for baseline Ki-67, Ki-67 change in controls, age, and body-mass index. No significant changes in phosphorylation of AKT or markers of insulin resistance after adjustment for treatment arm were seen. Interpretation: Undiagnosed insulin resistance or diabetes were common in our study population. Short-term presurgical metformin was associated with a reduction in Ki-67 proliferation index. We are now exploring the hypothesis that metformin reduces Ki-67 expression by inducing phosphorylation of AMP-activated kinase and subsequent mTOR proproliferative inhibition, independent of insulin and insulin-like growth factor receptor activation. Funding: Wellbeing of Women, Wellcome Trust.